Are intensive parental alienation treatments effective and safe for children and adolescents?. Issue 1 (2nd January 2019) - Mercer, Jean
Abstract: Strong claims have been made for the possibility of diagnostic discrimination between children who refuse contact with a nonpreferred divorced parent due to parental alienation (PA) created by the preferred parent and those who refuse for other reasons such as abuse. PA proponents have also argued that interventions, which include custody changes, can alter the alienated children's attitudes and create positive behavior toward the nonpreferred parent. This article examines the plausibility of PA diagnostic and treatment claims and relevant empirical evidence. It is concluded that PA advocates have failed to provide empirical support for the safety and effectiveness of their methods and that custody proceedings should take these facts into consideration. Future research directions based on established understanding of child development are suggested.